Du surveillant général cerné par les murs au conseiller principal d’éducation, passeur de frontières - Christine Focquenoy (Recherches en Éducation)
The General Supervisor who firmly enforced order and discipline in secondary schools in France in the nineteenth and twentieth century appeared in collective imagery as a strong character nicknamed the “surgé”, a relentless and repulsive character, guarding school walls. The “surgé” is generally represented as symbolizing a resented kind of discipline. Archival research together with interviews of former general supervisors were used to capture the historical profile of the general supervisor. They reveal a daily life confined by architectural, symbolical and hierarchal walls. The wall metaphorically reflects the educational relationship. The educational system meets the challenge of mass education (1950-1960). This very fertile environment gave birth to the educational advisor. This renaming emphasizes the real determination to shift from the 'good disciplinarian' of the 19th century to the educational advisor. We will nevertheless show that this new key character in the educational system is confronted to limits which alter his own professional identity. He inherits both the original cleavage between education and teaching and also the image of his 'ancestor' - the General Supervisor, the guard of the school walls. The gap - a spatiotemporal area specific to the Educational Adviser - is a source of discomfort for the staff but also that of productiveness to help go beyond boundaries.